Altered amygdala and hippocampus function in adolescents with hypercortisolemia: A functional magnetic resonance imaging study of Cushing syndrome - Maheu, Françoise S. (2008)
Chronic elevations of endogenous cortisol levels have been shown to alter medial temporal cortical structures and to be accompanied by declarative memory impairments and depressive symptoms in human adults. These effects of elevated endogenous levels of cortisol have not been directly studied in adolescents. Because adolescents with Cushing syndrome show endogenous elevations in cortisol, they represent a unique natural model to study the effects of prolonged hypercortisolemia on brain function, and memory and affective processes during this developmental stage. Using functional magnetic resonance imaging (fMRI), we compared 12 adolescents with Cushing syndrome with 22 healthy control adolescents on amygdala and anterior hippocampus activation during an emotional faces encoding task. None of these adolescents manifested depressive symptoms. Encoding success was assessed using a memory recognition test performed after the scan. The fMRI analyses followed an event-related design and were conducted using the SPM99 platform. Compared to healthy adolescents, patients with Cushing syndrome showed greater left amygdala and right anterior hippocampus activation during successful face encoding. Memory performance for faces recognition did not differ between groups. This first study of cerebral function in adolescents with chronic endogeneous hypercortisolemia due to Cushing syndrome demonstrates the presence of functional alterations in amygdala and hippocampus, which are not associated with affective or memory impairments. Such findings need to be followed by work examining the role of age and related brain maturational stage on these effects, as well as the identification of possible protective factors conferring resilience to affective and cognitive consequences in this disease and/or during this stage of cerebral development.